In situ micro-computed tomography to study microstructure and sublimation front during freeze-drying. (July 2021) - Gruber, S.; Vorhauer-Huget, N.; Foerst, P.
Highlights: New method to visualize freeze-drying kinetics in situ using high resolution X-Ray imaging. High resolution X-Ray imaging enables to visualize pore structure in situ during freeze-drying. Link between pore structure and structure of sublimation front offers new details. Abstract: In this study, a new method is presented to examine the freeze-drying process of frozen solutions in situ. By using a newly developed freeze-drying stage for high resolution micro-computed X-Ray tomography, the freeze-drying process can be investigated in more detail. For the proof of concept maltodextrin (c =0.05 w/w, c =0.2 w/w and c =0.3 w/w) and sucrose (c =0.2 w/w) solutions were used as model substances. The use of X-Ray radiography enables to analyze the drying kinetics, while X-Ray tomography describes the pore structure in more detail. The results are qualitatively compared and the proof of the concept will serve as a basis for further studies in the future.